Learning a new land : immigrant students in American society - Suárez-Orozco, Carola, 1957- (Belknap Press of Harvard University Press, 2008)
"Based on an interdisciplinary study that followed 400 newly arrived children from the Caribbean, China, Central America, and Mexico for five years, this book provides a compelling account of the lives, dreams, and frustrations of these youngest immigrants. Richly told portraits of high and low achievers are packed with unexpected ironies. When they arrive, most children are full of optimism and a respect for education. But poor neighborhoods and dull - often dangerous - schools can corrode hopes. The vast majority learn English - but it is the English of video games and the neighborhood, not that of standardized tests." "For some of these children, those heading off to college, America promises to be a land of dreams. These lucky ones have often benefited from caring mentors, supportive teachers, or savvy parents. For others, the first five years are marked by disappointments, frustrations, and disenchantment."--Jacket